Small interfering RNA induced transcriptional gene silencing in human cells - Morris, Kevin (Henry Stewart Talks, 2007)
How siRNAs mediate transcriptional gene silencing (TGS) in human cells, Histone methylation, Dependency on active RNA polymerase II mediated transcription, siRNA-mediated TGS, H3K9 and H3K27 methylation of the targeted EF1A promoter, Nuclear specific delivery of the siRNA, Antisense strand-specific siRNA-mediated TGS of EF1A, Targeting of the U3 region of the HIV-1 LTR/promoter, Antisense strand of siRNA EF2 interacts with FLAG-tagged DNMT3A and the tri-methylated H3K27 methyl mark, siRNA mediated targeting of genomic regions, RNA Pol-II function, Transcriptional gene silencing in human cells
Archived at 2020/08/13